2020
DOI: 10.4102/hsag.v25i0.1313
|View full text |Cite|
|
Sign up to set email alerts
|

Effort and reward imbalance factors motivating Namibian professional nurses to participate in continuous professional development: A confirmatory factor analysis

Abstract: Background To improve professional development, it is important to understand the motivational factors behind nurses’ participation in specific types of continuous professional development activities. Effort–rewards imbalance (ERI) posits an imbalance between high efforts spent at work and low rewards sometimes received in turn. However, professional nurses have various ERIs that can influence their reasons to participate in continuous professional development activities. Aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Intrinsic effort as a basic desire that encourages individuals to achieve various fulfillment needs through encouragement, interest, and desire [13]. Nurses with high commitment can improve their ability to be more professional and it is related to nurses' motivation [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intrinsic effort as a basic desire that encourages individuals to achieve various fulfillment needs through encouragement, interest, and desire [13]. Nurses with high commitment can improve their ability to be more professional and it is related to nurses' motivation [13].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the review results found, there are intrinsic factors that can increase the work motivation of nurses such as: potential development needs (knowledge and skills) [12,18,21], reward [12,13,19], nature of work [12,14,18], intrinsic effort [13,14], experience [17], commitment [13],…”
Section: Review Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the findings of this study were higher than those of some previous studies, which reported nurses’ knowledge of CPR at 60% (Adal & Emishaw, 2023). The differences in results may be attributed to poor education, a lack of refresher training, and the Nursing Council's reluctance to allow nurses to maintain their annual registration without proof of attending any CPD activities (Baloyi & Jarvis, 2020; Mbidi & Damons, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…CPR training is part of nursing training at both the undergraduate and postgraduate levels. In 2011, the Health Professions Council of Namibia (HPC) issued a directive that mandates all registered health professionals to successfully participate in a set of approved continuing education activities on an annual basis (Mbidi & Damons, 2020). Nevertheless, the extent to which nurses in Namibia have benefited from this compulsory directive in terms of acquiring the necessary knowledge and attitudes concerning CPR remains unknown.…”
Section: Review Of Literaturementioning
confidence: 99%